PEMANFAATAN DAUN JATI SEBAGAI PIGMEN WARNA CAT TEMBOK - Suhardi Effendy; Sulhadi Sulhadi; Teguh Darsono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The utilization of teak leaf extract containing carotenoids for natural dyes on the manufacture of wall paint. Teak leaf extract boiled with 350 ml of water until boiling and filtered with screen mash T100. As glue is used a blend of tapioca flour and lime tohor as much as 75 grams with composition ratio (1: 3, 1: 1,3: 1). As a solvent used mix aqudes, PVAc glue and white cement. In this research, the process of making paint is by mixing all the material from pigment, adhesive, and solvent until homogeneous. Paint quality is shown through viscosity test, adhesion and density. The results of this study indicate that the best paint formulation composition is found in adhesive variation with a ratio of 3: 1 which produces density 1,3 gr/ml, viscosity 0,26 poise and 95% adhesion. Keywords: teak leaves, wall paint, viscosity test, adhesion and density